Chronic oedema: a prevalent health care problem for UK health services - Moffatt, Christine J (Int Wound J, 2016)
Chronic oedema (CO) is a major clinical problem worldwide, which has many important secondary consequences for health, activity and participation. Effective treatment planning and organisation of services is dependent on an understanding of the condition and its epidemiology. This cross‐sectional study was designed to estimate the point prevalence of CO within the health services of one UK urban population and to determine the proportions that have concurrent leg ulceration. Patients with CO in all anatomic sites were ascertained by health care professionals in one acute and one community hospital, all relevant outpatient and community nursing services, general practices and all nursing/residential homes in one urban catchment area (Derby City). The presence and distribution of oedema was confirmed through a brief clinical examination. A battery of demographic and clinical details was recorded for each case. Within the study population of Derby City residents, 971 patients were identified with CO [estimated crude prevalence 3·93 per 1000, 95% confidence interval (CI) 3·69–4·19]. The prevalence was the highest among those aged 85 or above (28·75 per 1000) and was higher among women (5·37 per 1000) than men (2·48 per 1000). The prevalence among hospital inpatients was 28·5%. Only five (3%) patients in the community population had oedema related to cancer or cancer treatment. Of the 304 patients identified with oedema from the Derby hospitals or community health services, 121 (40%) had a concurrent leg ulcer. Prevalence statistics and current demographic trends indicate that CO is a major and growing health care problem.